Kejadian Preeklampsia Pada Ibu Hamil Terkait Dengan Distensi Rahim Dan Riwayat Penyakit - Alibasa, Sulistiani; Sagita, Yona Desni (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
Pre-eclampsia is a group of symptoms that arise in pregnant, childbirth and postpartum women consisting of hypertension, edema and proteinuria that appear at 20 weeks of gestation until the end of the first week after delivery. The research objective was to determine the correlation between uterine distension and disease history with the genesis of pre-eclampsia to the pregnant women at the Batin Mangunang Tanggamus Regional Hospital in 2020. The method in this research is quantitative research with case-control. The population in this research were all pregnant women recorded in medical records who performed check-up at the Batin Mangunang Tanggamus Regional Hospital in 2020 with a total sample of 86 people who had pre-eclampsia and 86 people who did not experience preeclampsia. The analysis used univariate and bivariate by using the chi-square test. The results of the research prove that there is a correlation between uterine distension (p-value = 0.000) and history of the disease (p-value = 0.001) with the genesis of pre-eclampsia to the pregnant women at the Batin Mangunang Tanggamus Regional Hospital in 2020. Health workers should continue to improve counselling by providing pamphlets in the obstetrics room about the genesis of pre-eclampsia and its causative factors, in order to increase the knowledge of pregnant women, so that the occurrence of pre-eclampsia can be avoided early on.